Library capacity for data curation services: a US national survey. Issue 4 (27th June 2019) - Yoon, Ayoung; Donaldson, Devan Ray
Abstract : Purpose: The purpose of this paper is to understand the landscape of data curation services among public and academic libraries in the USA, with a focus on library capacity for providing data curation services. Design/methodology/approach: The authors conducted an online survey by employing stratified sampling from the American Library Directory. A total of 198 responses were analyzed. Findings: The authors' findings provide insight into the current landscape of libraries' data curation services. The survey participants evaluated six capacity dimensions for both public and academic libraries – value, financial, administrative, technical infrastructure, human resources and network. The ratings the participants gave to these capacity dimensions were significantly different between academic and public libraries. Practical implications: This study suggests several areas in which libraries will benefit from further developing their capacity to successfully run data curation services. Originality/value: This is among the first research study to address the concept of capacity in the context of libraries' data curation services.